3: IGF-1 Hydrogel-based Nanofiber Drug Delivery System to Improve Nerve Regeneration and Functional Recovery After Peripheral Nerve Repair. (July 2021) - Harris, Thomas G.W.; Qiu, Chenhu; Sarhane, Karim; von Guionneau, Nicholas; Glass, Connor; Segna, Kara; Wong, Alison; Hanwright, Philip; Malapati, Harsha; Hricz, Nicholas; Generoso, Matthew; Hōke, Ahmet; et al.
Abstract : Purpose: Insulin-like growth factor 1 (IGF-1) is a potent mitogen with the potential to enhance axonal regeneration and minimize muscle atrophy and Schwann cell senescence following prolonged denervation after peripheral nerve injury. IGF-1 is a small protein with a half-life of 5 min, making local delivery a challenge. Our group has demonstrated over 6 weeks of sustained release of bioactive IGF-1 encapsulated within biodegradable nanoparticles (NP) and subsequently developed a nanofiber fiber hydrogel composite (NHC) carrier to retain IGF-1 NPs at target tissue locally for the duration of drug release. The aim of this study was to further characterize and refine the IGF-1 NP-NHC drug delivery and then investigate its efficacy in both rodent and non-human primate (NHP) median nerve injury models. Methods: IGF-1 was encapsulated in biodegradable PCL NPs and then embedded within the NHC composed of hyaluronic acid and PCL nanofibers. Release kinetics and biocompatibility were evaluated and optimized both in vitro and in vivo . The drug delivery system was assessed using a chronic denervation median nerve injury rat model and an acute median nerve repair NHP model. IGF-1NP/NHC was injected along the median nerve and within denervated muscle. In rodents, a range of IGF-1 doses (300, 900 and 1500 μg/mL) were investigated to evaluate dose-response relationships. Axonal regeneration, muscle atrophy, neuromuscular junction reinnervation and recovery of grip strength were assessed. Results: The refined NP-NHC delivery system provided sustained release of bioactive IGF-1, in vivo, for at least 42 days by serial ELISA. IGF-1 treated rodents demonstrated a 35% increase in functional recovery (stimulated grip strength) compared to untreated rodents, with no differences observed between the different concentrations of IGF-1 that were evaluated. Median nerve histomorphometry demonstrated a significantly greater total number of axons at each concentration of IGF-1 compared to untreated rodents (p<0.0001). IGF-1 treated rodents also demonstrated a greater percentage of reinnervation of neuromuscular junctions by 17% (from 14% to 31%). In addition, the IGF-1 treated non-human primate demonstrated a 31% increase in functional recovery compared to the untreated animal (N=1 per group). Conclusion: The IGF-1 NP/NHC delivery system provided sustained delivery for over 42 days in rodents and NHP. IGF-1 improves motor functional recovery by enhancing axonal regeneration and neuromuscular junction reinnervation while limiting denervation-induced muscle and Schwann cell atrophy in rodents. Our NHP pilot study has established a used pre-clinical model with robust functional analysis that will serve as a platform for a formal NHP study prior to clinical testing. The components of the NP-NHC delivery system are already used in FDA approved formulations, which will facilitate clinical translation.